Ceremony - Silko, Leslie Marmon, 1948- (Penguin classics deluxe edition., 2006)
Tayo, a young Native American, has been a prisoner of the Japanese during World War II, and the horrors of captivity have almost eroded his will to survive. His return to the Laguna Pueblo reservation only increases his feeling of estrangement and alienation. While other returning soldiers find easy refuge in alcohol and senseless violence, Tayo searches for another kind of comfort and resolution. Tayo's quest leads him back to the Indian past and its traditions, to beliefs about witchcraft and evil, and to the ancient stories of his people. The search itself becomes a ritual, a curative ceremony that defeats the most virulent of afflictions -- despair.